2009
DOI: 10.1210/jc.2009-0337
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism Risk in Men Treated for Childhood Cancer

Abstract: Adult male survivors of childhood cancer are at risk of hypogonadism, which should be acknowledged in the long-term follow-up of these men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 30 publications
(38 reference statements)
5
49
1
Order By: Relevance
“…64 Given the potential morbidity associated with this complication and the availability of effective treatments, continuation of this screening may be prudent. 65 The prevalence of Leydig cell dysfunction in childhood cancer survivors has ranged from 2% to 23%, [66][67][68][69] lower than the prevalence identified in our study (32%). This may reflect the higher proportion of at-risk patients with a history of HCT (52%) in our cohort, a large proportion of whom received testicular irradiation (48%), and the fact that our cohort included only those at risk for the complication because of gonadotoxic therapeutic exposure.…”
Section: -56contrasting
confidence: 55%
“…64 Given the potential morbidity associated with this complication and the availability of effective treatments, continuation of this screening may be prudent. 65 The prevalence of Leydig cell dysfunction in childhood cancer survivors has ranged from 2% to 23%, [66][67][68][69] lower than the prevalence identified in our study (32%). This may reflect the higher proportion of at-risk patients with a history of HCT (52%) in our cohort, a large proportion of whom received testicular irradiation (48%), and the fact that our cohort included only those at risk for the complication because of gonadotoxic therapeutic exposure.…”
Section: -56contrasting
confidence: 55%
“…In a similar study of 32 male CLSs Romerius et al [19] showed a prevalence of hypogonadism of 31% (10 of 32) compared to 4% in healthy controls. In a study of adult lymphoma survivors with a median age of 33 years at diagnosis, the prevalence was 31% [4].…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, Leydig cell dysfunction may be observed following treatment with alkylating agent regimens, with some reports indicating that from 10 to 57% of male subjects can develop elevated serum concentrations of LH following treatment (Bramswig et al 1990, Siimes et al 1995, Heikens et al 1996, Mackie et al 1996, Papadakis et al 1999, Sklar 1999, Relander et al 2000, Kenney et al 2001, Romerius et al 2009). When it does occur, chemotherapy-induced Leydig cell dysfunction is generally subclinical (Afify et al 2000, Bakker et al 2004, Sanders 2004.…”
Section: Leydig Cell Dysfunctionmentioning
confidence: 99%